2003
DOI: 10.1021/jo034734g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Naturally Occurring Acetylenes via an Alkylidene Carbenoid Rearrangement

Abstract: Naturally occurring mosquito larvicidal acetylenes 1 and 2, and analogues 3 and 4, each containing either a 1,3-butadiynyl or a 1,3,5-hexatriynyl moiety, are synthesized via a Fritsch-Buttenberg-Wiechell rearrangement. The alkylidene carbenoid intermediate results from lithium-halogen exchange of a suitable dibromoolefin precursor, and the rearrangement is accomplished under mild conditions. Synthesis of the dibromoolefin precursors to acetylenes 1-4 is easily achieved in three steps from commercially availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
0
17
0
5
Order By: Relevance
“…In cases in which the pendant functionality was an aryl group (45a-c), the resulting ketones were surprisingly unstable and were converted directly into dibromoolefins (46a-c). Ketones with alkenyl substitution (45d-g) showed greater stability and could be isolated pure and fully characterized prior to elaboration to 46d-g. Rearrangement of 46a-g in hexanes gave conjugated triynes 47a-g under standard conditions [34][35]. …”
Section: Triynes From Acid Chloridesmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases in which the pendant functionality was an aryl group (45a-c), the resulting ketones were surprisingly unstable and were converted directly into dibromoolefins (46a-c). Ketones with alkenyl substitution (45d-g) showed greater stability and could be isolated pure and fully characterized prior to elaboration to 46d-g. Rearrangement of 46a-g in hexanes gave conjugated triynes 47a-g under standard conditions [34][35]. …”
Section: Triynes From Acid Chloridesmentioning
confidence: 99%
“…Bohlmann's initial synthesis of 57 relied on the derivatization of a highly reactive triynal precursor [48]. A reported alternative synthesis of compound 57 involves only three steps from acid chloride 58, which is generated quantitatively from the commercially available carboxylic acid [35]. A typical sequence of Friedel-Crafts acylation (59) and dibromoolefination provides the necessary precursor 60, and the final FBW rearrangement with 60 proceeds nicely to give enetriyne 57 in 84 % yield.…”
Section: Natural Products Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[36] Advancing the scope of the FBWr required dibromoolefins as precursors, and these are readily available through a number of routes using standard transformations. [30,33] In the couple of years following our initial discovery, general approaches using the FBWr were developed to give (Table 1), for example, di-, tri-, and tetraynes (master's student Annabelle Shi Shun and undergraduate Erin Chernick), [33,37] natural product analogues, [35,38,39] polyyne sugars (in collaboration with my colleague in Alberta, Todd Lowary, and graduate students Thanh Luu and Wei Shi), [34] and a "one-pot" protocol to functionalized polyynes (developed by Yasuhiro Morisaki, a postdoc visiting from Professor Chujo's group in Kyoto). [38,40] It turns out that our "discovery" came just in time.…”
Section: Introductionmentioning
confidence: 99%
“…Desilylation of acetylenic compounds can be performed with the use of various reagents, among which such bases as alkali metal hydroxides [6], alkoxides [7], and carbonates [8] in protophylic solvents, as well as potassium [9] and ammonium fluorides [10] are used most frequently. We recently showed that successful desilylation may be achieved with the aid of even weak bases generated in protic medium from metal oxides (PbO 2 , MnO 2 , Co 2 O 3 , Ni 2 O 3 ) [11].…”
mentioning
confidence: 99%